Best Answer

-14 + 3p = -9p - 21

add 14 and 9p to both sides, then 12p = -7

p = -7/12

Q: -14 plus 3p equals -9p-21

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7

-9p + 6p = -3p

3p = 2p + 12subtracting 2p from both sidesp = 12 ■

p = -1

First get all the p variables on one side of the equation by subtracting 6p from both sides. Giving you 3p + 14 = 23 Now subtract 14 from both sides. 3p = 9 Finally divide both sides by 3. p = 3

Related questions

3p plus 7 equals 34, where P is equivalent to number 9.

3p+7 = 16+2p 3p-2p = 16-7 p = 9

3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7

-9p + 6p = -3p

4p+2 = 3p-7 4p-3p = -7-2 p = -9

3p = 2p + 12subtracting 2p from both sidesp = 12 ■

p = -1

13 + 3p = -2subtract 13 from each side, 3p = -15divide each side by 3, p = -5

p+2 = 2-3p p+3p = 2-2 4p = 0 p = 0

First get all the p variables on one side of the equation by subtracting 6p from both sides. Giving you 3p + 14 = 23 Now subtract 14 from both sides. 3p = 9 Finally divide both sides by 3. p = 3

16p + 6q - 3p - 8q = (16p - 3p) + (6q - 8q) = 13p -2q

p=1